Relevansi Gerakan Anti Korupsi Untuk Pembangunan - Yuni Retnowati; Yenni Sri Utami (Jurnal Paradigma, 2014)
Culture corruption in Indonesia happened since the former kingdom until now. In 2010, Indonesia becoming a nation most corrupt in the Asia Paci c region. Corruption ourished in Indonesia because of politics and economic factors, and Javanese culture. Corruption is differentiated into grand corruption, state capture and petty corruption. In addition to the effect on economic growth and investment, corruption also weakens the ability of the Government in carrying out its development programs. Facing the impact of corruption that af ict people then appeared a various anti-corruption movement either come from the government or from society. Purpose of many efforts to ght against corruption is improving the welfare of people which also became national development goal